Improvisation of an Optical Pressure Sensor Based Dynamic Foot Pressure Measurement System (Bangladesh Journal of Medical Physics, 2013)
Dynamic foot pressure measurement is necessary particularly for diabetic patients to prevent ulcers, eventually leading to gangrene and amputation. The present work reports a low cost optical sensing system for the above, suitable for the Third World. It uses a horizontally placed transparent Acrylic plate with a webcam placed below facing upwards. A white paper, backed by a black adhesive plastic sheet, covered the whole plate on the top. Light from a tubular fluorescent lamp entered the acrylic plate from a side and traversed the thickness through total internal reflection. At points of pressure applied from the top, the air between the paper and the acrylic plate got displaced and caused breakdown of total internal reflection. The scattered light rays from the white sheet were recorded by the webcam. Computer software on Java platform was developed to grab and analyse video data to display dynamic pressure distribution in artificial colour contours. Approximate pressure calibration was obtained using static and dynamic values obtained from subjects with normal and abnormal foot pressures. Time graphs of pressure at user chosen points were also provided. The developed system worked with satisfaction and is being used for clinical assessment regularly. DOI: http://dx.doi.org/10.3329/bjmp.v4i1.14687 Bangladesh Journal of Medical Physics Vol.4 No.1 2011 51-58